The AIR Learning Model (Auditory, Intellectual, Repetition): Its Effectiveness in Enhancing Student Learning Engagement - Sholehah, Tika Fahmiyati; Asiah, Nur; Yusnita, Erni (Journal of Innovation and Research in Primary Education, 2025)
Student engagement in learning represents a critical indicator of educational quality, yet many Islamic Religious Education programs continue to struggle with low participation rates and passive learning environments. This study investigated the effectiveness of the AIR (Auditory, Intellectual, and Repetition) learning model in enhancing student learning engagement, specifically focusing on students' ability to express ideas during classroom activities. A quasi-experimental design with posttest-only control group was employed involving 62 Grade XI students at SMK Nurul Falah Pugung, Indonesia. Participants were randomly assigned to experimental (n=31) and control (n=31) groups, receiving AIR model instruction and conventional direct instruction respectively. Learning engagement was measured using a validated questionnaire focusing on the "expressing ideas" indicator, demonstrating acceptable reliability (Cronbach's α = 0.701). Data analysis included normality and homogeneity testing followed by independent samples t-test. The experimental group demonstrated significantly higher learning engagement scores (M = 23.45, SD = 3.12) compared to the control group (M = 20.87, SD = 2.98). Statistical analysis revealed significant differences between groups (t(60) = 3.456, p = 0.011 < 0.05) with a large effect size (Cohen's d = 0.89), indicating both statistical and practical significance of the intervention. The AIR learning model effectively enhances student engagement by integrating auditory, intellectual, and repetition components that address behavioral, cognitive, and emotional engagement dimensions. The findings contribute to educational theory by validating innovative pedagogical approaches in religious education contexts and provide practical frameworks for transforming passive learning environments into interactive, student-centered experiences that prepare students for contemporary educational and workplace demands.